ANALISIS KARAKTERISTIK DAN KEBUTUHAN BELAJAR PESERTA DIDIK TERHADAP PERENCANAAN PEMBELAJARAN DI SEKOLAH DASAR - Bachtian Rudin, Raka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to analyze the characteristics of elementary school students in relation to their learning needs. The background of this study is the diversity of cognitive, socio-emotional, physical, moral, and motivational characteristics of students, which often pose challenges in implementing effective learning at the elementary school level. The purpose of this study was to identify dominant student characteristics and determine how these characteristics reflect students' learning needs. This study used a quantitative descriptive approach. Data were collected using questionnaires distributed to elementary school students from several schools as the research sample. The collected data were analyzed by calculating the percentage of responses for each statement in the same indicator to identify dominant tendencies. The results showed that students tended to have a high level of curiosity and preferred learning through visual aids and real-life examples. Students also showed higher learning motivation when lessons were presented in an interesting, fun, and contextual manner. In addition, students demonstrated good socio-emotional development, such as obeying school rules and enjoying collaborative learning, as well as a strong preference for physical activities, including movement, play, and maintaining personal hygiene. From a moral and spiritual perspective, students demonstrated positive habits such as praying before and after learning activities and apologizing when making mistakes. These findings indicate that learning in elementary schools must be designed holistically and contextually to accommodate students' characteristics and learning needs in order to create meaningful and effective learning experiences.